Analisis Kasus Persekongkolan Tender dalam Pelanggaran Undang-Undang Nomor 5 Tahun 1999 Tentang Larangan Praktek Monopoli dan Persaingan Usaha Tidak Sehat - Yacub, Tifanny Nur (Journal Social Sciences and Humanioran Review, 2024)
In Indonesia, rampant bid rigging has hindered economic growth. This study investigates business competition in Indonesia with a particular emphasis on bid rigging and the implementation of Law No. 5/1999 which prohibits monopolistic practices and unfair business competition. The issue raised is how effective law enforcement and supervision are against the practice of bid rigging. Normative or doctrinal research is conducted using statutory and conceptual approaches. The relevant laws and regulations and literature were studied before data was collected. The results show that tender rigging still occurs, especially in the procurement of goods and services by companies, although Law No. 5 Year 1999 establishes a legal framework to prevent monopolistic practices and unfair business competition. One of the solutions offered is to improve supervision through adequate infrastructure; stricter sanctions; raising awareness of the importance of fair business competition; and increasing the transparency of the tender process through e-procurement. This study concludes that to create a healthy working environment, concrete and integrated actions are needed. It is recommended that relevant agencies work better together and that there is consistent law enforcement.